Professionalism, Experience, and Organizational Commitment: Determining Factors of Internal Auditors’ Performance Quality at the Inspectorate Office of Pekanbaru - Hasibuan, Rezki Purnama Sari; Suci, Rama Gita; Putri, Adriyanti Agustina; Irman, Mimelientesa (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2023)
This study aims to examine the influence of professionalism, experience, and organizational commitment on the quality of internal auditors’ performance. This research employs a quantitative approach, with data collected through questionnaires. The population consists of all auditors working at the Inspectorate Office of Pekanbaru City. The sampling technique used is probability sampling, resulting in 32 respondents who participated in the study. Data were analyzed using multiple linear regression and processed with SPSS version 26. The results show that professionalism and organizational commitment have a significant effect on the quality of internal auditors’ performance, while experience does not have a significant effect.